Kampung Budaya: Upaya PT Pertamina EP Jambi Field dalam Meningkatkan Pendidikan Suku Anak Dalam - Afrianto, Afrianto; Arifin, M. Zainul; Hidayah, Lutfia Nur; Safrida, Safrida (Journal of Administration, Governance, and Political Issues, 2024)
Suku Anak Dalam (SAD), a part of the Remote Indigenous Communities (KAT), faces significant social challenges, particularly in access to education. To address this, PT Pertamina EP Jambi Field has initiated the "Kampung Budaya" program as part of its Corporate Social Responsibility (CSR) efforts in Hajran Village, Batang Hari Regency, Jambi Province. This study aims to explore the impact of the Kampung Budaya program on the educational empowerment of SAD children. Utilizing a qualitative approach, data were collected through in-depth interviews with three key informants: a local hero, an adat leader (waris), and a community figure. The findings demonstrate that the program represents a form of planned social change, focusing on educational transformation at the micro level through the provision of learning activities and infrastructure development. The intervention has contributed to increased knowledge, improved attitudes, and behavioral shifts among SAD children. PT Pertamina EP Jambi Field recognizes that fostering change within traditional communities, like the SAD, is a long-term process, particularly when it involves cultural beliefs. This program is an initial step towards broader social transformation and fulfilling the fundamental rights of the SAD community, indicating the company’s role as an agent of change at both micro and macro levels.